Socio-economic profile of pure - bred dog owners in Puducherry - V. Rajaganapathy, Raghy Radhakrishnan, D. Sreekumar S. Ramkumar, Ninan Jacob (Indian Journal of Animal Production and Management, 2019)
A study was carried out to assess the socio-economic profile of pure - bred dog owners in Puducherryregion of the Union Territory of Puducherry. 150 dog owners were selected as respondents who owned164 dogs of different breeds.The mean age of the dog owners was 40.04 years. Male members of thehousehold were reported to be the owners of the dog in the majority of the households. Majority of themwere graduates and working in private sector. Their experience in dog rearing was 7.26 years on an average,and the average number of dogs owned per household was 1.09 dogs. The average age of the dog was37.55 months at the time of the study, and male dogs were more than female dogs.